Does economic distance affect the flows of trade and foreign direct investment? Evidence from Vietnam - Thai-Ha Le (Cogent Economics & Finance, 2017)
This study examines the effect of relative economic distance (RED) between countries on bilateral foreign trade and foreign direct investment (FDI), using Vietnam as a case study. The difference in per-capita GDP is used as proxy for the RED between Vietnam and her partner countries. Modified gravity models are estimated using the procedure of panel-corrected standard errors (PCSE). The results indicate that there is a feedback and significantly positive relationship between Vietnam's trade and FDI inflows. The economic distance between Vietnam and her partner countries has a significantly positive influence on the country's bilateral trade and FDI inflows.
Keywords: C23; F1; F21; 330; economic distance; trade; foreign direct investment; panel-corrected standard errors; Vietnam